Orbital complications of sinusitis in children in Komfo Anokye Teaching Hospital - Opoku-Buabeng, Joseph; Yaw Lartey, Seth (ENT Updates, 2017)
Objective: To evaluate the pattern and incidence of orbital complications due to sinusitis in children in Komfo Anokye Teaching Hospital. Methods: Ninety-two children aged between 2 and 14 years who presented with various orbital complications as a result of sinusitis among 1627 children in a 5-year period were evaluated to analyze the pattern and the incidence of the various stages and forms. Results: Of the 1627 children evaluated, 92 (5.7%) had orbital complications. Among those with complications, 52.2% presented with orbital cellulitis, 22.8% presented with subperiosteal abscess, 14.1% presented with periorbital cellulitis, 8.7% presented with orbital abscess, and 2.2% presented with cavernous sinus thrombosis. Conclusion: Despite the low incidence of sinogenic orbital complications, this study showed that orbital cellulitis is the most common among all orbital complications as a result of sinusitis in children.